piRNA production requires heterochromatin formation in Drosophila - Rangan, Prashanth (2011)
Protecting the genome from transposable element (TE) mobilization is critical for germline development. In Drosophila, Piwi proteins and their bound small RNAs (piRNAs) provide a potent defense against TE activity. TE targeting piRNAs are processed from TE-dense heterochromatic loci termed ‘piRNA clusters’. While piRNA biogenesis from cluster precursors is beginning to be understood, little is known about piRNA cluster transcriptional regulation. Here we show that deposition of histone 3 lysine 9 by the methyltransferase dSETDB1 (egg) is required for piRNA cluster transcription. In the absence of dSETDB1, cluster precursor transcription collapses in germline and somatic gonadal cells and TEs are activated, resulting in germline loss and a block in germline stem cell differentiation. We propose that heterochromatin protects the germline by activating the piRNA pathway.